Differential impacts of compound dry- and humid-hot events on global vegetation productivity - Liu, Meng; Yu, Han; Duan, Wenzhuo; Wu, Mousong (Frontiers in Environmental Science, 2025)
IntroductionThe increasing frequency of compound heat events (CHEs), including compound dry-hot events (CDHEs) and compound humid-hot events (CHHEs), poses significant threats to terrestrial ecosystems. While previous studies have examined the independent and combined effects of drought and heat on vegetation productivity, the specific roles of CHHEs and the differential impacts of CDHEs and CHHEs remain poorly understood.MethodsUsing Gross Primary Productivity (GPP) estimated from satellite-based near-infrared reflectance (NIRv), monthly meteorological data and the Standardized Precipitation Evapotranspiration Index (SPEI), this study calculated the Standardized Compound Event Indicator (SCEI) to quantify the severity of CHEs, and investigated the immediate and lagged effects of CDHEs and CHHEs on global GPP from 2001 to 2018.ResultsOur results demonstrated that CDHEs occurred more frequently and with greater severity than CHHEs during the study period. The immediate effects of CDHEs reduced GPP in 68% of vegetated areas, whereas CHHEs enhanced GPP in 58% of vegetated areas. Globally, CDHEs and CHHEs caused net GPP changes of −5.26 Pg C yr−1 and 1.67 Pg C yr−1, respectively. In contrast, GPP in the polar zone, boreal shrubs, and boreal grasslands increased during CDHEs and decreased during CHHEs, with average net GPP changes of 0.17 Pg C yr−1 and −0.04 Pg C yr−1, respectively. Additionally, lag effects were most prominent in the periods of 0 to 3 months and 10 to 12 months post-event.DiscussionThese findings highlight the contrasting impacts of compound dry- and humid-hot events on ecosystem carbon fluxes and provide a better understanding of global carbon cycles under climate extremes.